128: DECIPHERING THE IMMUNOLOGICAL DETERMINANTS OF RESPONSE TO NEOADJUVANT CHEMO-RADIATION IN ESOPHAGEAL ADENOCARCINOMA. (23rd April 2022) - Arbore, G; Albarello, L; Bucci, G; Punta, M; Bilello, V; Bonfiglio, S; Fanti, L; Cossu, A; Tonon, G; Rosati, R; Casorati, G; Dellabona, P
Abstract: Background and aim: The standard therapy for esophageal adenocarcinoma (EAC) is pre-operative neoadjuvant chemo-radiation (NACR) and surgery. Less that 30% of patients achieve a pathological complete response (pCR) and increased 5-year survival after NACR. Understanding the mechanisms of response to NACR is pivotal to better stratify patients and inform the design of more efficacious therapies. Cancer progression partly depends on defective immune surveillance, and the presence of tumor infiltrating T lymphocytes (TILs) is associated with better prognosis of several malignancies. We hypothesize that NACR induces immunogenic cell death that stimulates immune responses against tumor neoantigens (TNAs), derived from cancer somatic mutations, in the responders. We thus compared responders and non-responders for tumor immune contexture, immune molecular pathways, circulating immune markers and TNAs-specific T cells responses. Methods: Pre-NACR tumor biopsies prospectively collected from consecutive EAC patients were subjected to DNA whole exome and RNA sequencing, high dimensional (HD) multiparametric flow cytometry and immune contexture analysis by histology and by proteome digital spatial profiling (n = 53 targets), while their peripheral blood mononuclear cells and plasma collected pre- and post- NACR were analyzed by HD flow cytometry and cytokine multiplexing assay respectively. Results: Treatment-naïve EACs of NACR responders showed higher TNA load and enriched immune signatures compared to non-responders. Moreover, pre-treatment EACs of responders demonstrate augmented effector T cell infiltration and reduced Treg cells and M2-like pro-tumoral macrophages. High M2-like macrophages score associated with lower overall survival. Increased frequencies of circulating myeloid suppressor populations were detected both at baseline and after NACR in non-responder patients. These observations were associated with circulating levels of n = 30 cytokines/chemokines and with spatial expression of immune markers in tumor biopsies. Conclusion: Collectively, these results support pre-existing immune-mediated mechanisms of anti-tumor response stimulated by NACR in the fraction of responder EAC patients, suggesting possible ways to stratify patients and direct them to more tailored neoadjuvant and/or adjuvant treatments, possibly in combination with personalized immunotherapy approaches.